Simulation Biomass Effecting On Microbial Fuel Cell Electricity Properties and Substrate Degradation - Xingguan Ma; Jiao Wang; Xiangxin Xue; Yulan Tang; Jinxiang Fu (Institute of Advanced Engineering and Science, 2013)
Microbial fuel cell (MFC) mathematical model was established with suspended microorganisms, biomass on the electrode material, soluble chemical substrates and intermediary. By simulating the process of the substrate degradation, biomass growth and the electric current production process, With different initial biomass concentration, suspended microbial biomass and biomass attaching on electrode varing with time,current and charge varing with time,substrate concentration varing with time and mediator concenration varing with time were investigated. The results showed that initial suspended microbial is little, growth of biomass is main on electrode, biomass in solution grow slowly, producing electricity the main function biomass is on electrode, while initial suspended microbial concentration is high, growth of biomass is main in solution, biomass on electrode grow slowly, producing electricity the main function biomass is in solution; the more initial suspended microbial, the faster current reaching the maximum, the more charge, the faster substrate degradation, the faster mediator variation; initial add biomass benefit to MFC producing electricity. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1977